The Role of Skin and Gut Microbiome in Atopic Dermatitis - Menul Ayu Umborowati, MD; Nurdini Wilda Salsabila, MD; Damayanti, MD, PhD; Sylvia Anggraeni, MD; Prof. Cita Rosita Sigit Prakoeswa, MD, PhD (Journal of Pakistan Association of Dermatologists, 2022)
In the last decade, there has been an increase in atopic dermatitis (AD) worldwide. AD is a chronic inflammatory skin disease characterized by mild to severe itching, recurrent, and mostly occurred in infancy and childhood. There were some substantial data of patients with AD that have been disturbed and less diverse skin and gut microbes than healthy individuals. AD is known to possess a higher proportion of Staphylococcus aureus (S. aureus) in the skin microbiome than healthy individuals. In addition, the population of Clostridium difficile, Escherichia coli, and Staphylococcus aureus in the gastrointestinal tract of patients with AD is higher than normal individuals, whereas the population of Bifidobacteria, Bacteroidetes, and Bacteroides are experienced a decrease. The AD will be prevented or treated if there is a balance in the gut and skin microbiome. It seems to underlie the benefit of probiotic in AD management.